Mortality in Patients on Renal Replacement Therapy and Permanent Cardiac Pacemakers - Gabriel Vanerio; Cristina García; Carlota González; Alejandro Ferreiro (International Journal of Nephrology)
End stage renal disease is a relatively frequent disease with high mortality due to cardiac causes. Permanent pacemaker (PM) implantation rates are also very common; thus combination of both conditions is not unusual. We hypothesized that patients with chronic kidney disease with a PM would have significantly higher mortality rates compared with end stage renal disease patients without PM. Our objectives were to analyze mortality of patients on renal replacement therapy with PM. 2778 patients were on renal replacement therapy (RRT) and 110 had a PM implanted during the study period. To reduce the confounding effects of covariates, a propensity-matched score was performed. 52 PM patients and 208 non-PM matched patients were compared. 41% of the PM were implanted before entering the RRT program and 59% while on RRT. Mortality was higher in the PM group. Cardiovascular disease and infections were the most frequent causes of death. Propensity analysis showed no differences in long-term mortality between groups. We concluded that in patients on RRT and PM mortality rates are higher. Survival curves did not differ from a RRT propensity-matched group. We concluded that the presence of a PM is not an independent mortality risk factor in RRT patients.